Perennial grass composition as an indicator of condition of Southwestern mixed grass ranges - Canfield, R.H. (Ecology, 1948)
Events usually record their own history. Main results stand forth boldly but the signs that foreshadow them often are unnoticed. So it is with the marks left by good and poor range management. Realizing the range can tell its own story best, range managers have come to rely on indicators that may be observed on the ground and which reflect the condition of the range (Talbot, '37). Among the commonly noted indicators of the condition of the range is density of forage plant cover, whether unpalatable and noxious plants occur in normal or abnormal abundance, and the absence or presence of accelerated soil erosion. Usually these indicators are evidence of a condition already existing. In the Southwest, often they fail to indicate early stages of range recovery or to forewarn of impending range deterioration. For example, unpalatable, deep-rooted shrubs are less important in indicator value than perennial grasses because they may move in slowly on overused ranges and often persist even though the grass cover has improved under good range management. Investigations conducted on the Santa Rita Experimental Rangeshow that the native grasses exhibit marked individuality in their response to various intensities of grazing and, thereby, indicate the early stages of trend either toward range recovery or toward range deterioration. This phenomenon is possible because the perennial grasses bear the brunt of grazing and, therefore, shows an earlier response than do lightly grazed or nongrazed associated plants. The present condition of grazing lands indicates there is a serious need for additional guides or criteria on which needed changes in range management can be made. The purpose of this article is twofold: (1) To present data regarding the floristic composition of perennial grass population as indicators of range recovery and range deterioration on mixed grass ranges of southern Arizona. (2) To portray the characteristic perennial grass patterns resulting from different grazing treatments on two specific range types on the Santa Rita Experimental Range in order to aid in the recognition of similar relationships on comparable ranges.
Keywords: density of forage plant cover; indicator; perennial grass composition; range condition